Profile and differences in financial literacy: empirical evidence - Mokhtar, Nuradibah; Sabri, Mohamad Fazli; Ho, Catherine S. F.; Moga Dass, Thinagaran (Malaysian Consumer and Family Economics Association, 2018)
The increasing cost of living in Malaysia has resulted in individuals and households being more mindful of their wealth management. Financial crises and world geopolitical issues have caused much volatility in returns and market volatility. These economic challenges have impacted the way Malaysians save, spend, manage risks and invest in order to preserve their livelihood. It is therefore vital to understand financial instruments and markets in order to better manage investments and wealth. This research aims to study the level of financial literacy among Malaysians across gender, income, age and ethnicity group. It applies a quantitative study method with a self-administered questionnaire to obtain relevant data. A total sample of 2000 respondents is obtained and results reveal that unfortunately, the majority of Malaysians possess only moderate level of financial literacy. In addition, there are significant differences in female, who are in the above the RM7000 income group, 30 to 39 years old and Chinese in terms of financial literacy. Findings from the study provide a better understanding of the level of Malaysians" financial literacy and implication on policy objectives to further strengthen this area through targeted sustainable financial education.